2014
DOI: 10.1016/j.neubiorev.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and the two-hit hypothesis of schizophrenia

Abstract: The high societal and individual cost of schizophrenia necessitates finding better, more effective treatment, diagnosis, and prevention strategies. One of the obstacles in this endeavor is the diverse set of etiologies that comprises schizophrenia. A substantial body of evidence has grown over the last few decades to suggest that schizophrenia is a heterogeneous syndrome with overlapping symptoms and etiologies. At the same time, an increasing number of clinical, epidemiological, and experimental studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
174
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(203 citation statements)
references
References 397 publications
5
174
0
11
Order By: Relevance
“…Environment and genetic factors play significant roles in SCZ (3)(4)(5). Environmental factors, including redox imbalance (4), inflammation (6) or obstetrical complications (7), have been reported to be associated with SCZ. Family, twin and adoption studies have shown that the genetic components increased the risk of SCZ (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Environment and genetic factors play significant roles in SCZ (3)(4)(5). Environmental factors, including redox imbalance (4), inflammation (6) or obstetrical complications (7), have been reported to be associated with SCZ. Family, twin and adoption studies have shown that the genetic components increased the risk of SCZ (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory markers have been identified in plasma as well as brain before and during the onset of psychotic symptoms in schizophrenia [3][4][5] ; if these contribute to the disease process, then anti-inflammatory treatments may attenuate the severity of schizophrenia. 6 5-HT 3 receptors are widely distributed in the brain, including in limbic and frontal cortical areas.…”
Section: Mechanismsmentioning
confidence: 99%
“…Emerging evidence also suggests that inflammatory processes may be involved in the etiopathogenesis of psychosis. (Feigenson et al, 2014) We therefore hypothesized that GGT will be linked to the development of psychosis. In this context, we aimed to assess the association of GGT with risk of psychosis, using a population-based cohort of 2,341 men free from any apparent mental illness at baseline from eastern Finland.…”
mentioning
confidence: 99%
“…Over the last few decades, emerging evidence suggests that chronic inflammatory processes (Benros et al, 2011;Feigenson et al, 2014) as well as oxidative stress (Owe-Larsson et al, 2011) may be involved in the pathogenesis of psychotic disorders. Whether GGT has a direct role in the pathogenesis or may just be a marker of underlying pathology, is not clear.…”
mentioning
confidence: 99%